STUDI KELAYAKAN PEMBANGUNAN INSTALASI PENGOLAHAN AIR TIPE REVERSE OSMOSIS UNTUK SUMBER AIR PERMUKAAN DI KOTA BALIKPAPAN - Widya Mulya (Universitas Lambung Mangkurat, 2021)
Water sources that can be utulized in large quantities by water treatment plants come from surface water, namely rivers. Water is a basic need for life, the increase in population is followed by the rate of use, the burden of populations is also increasing rapidly. Based on data from PDAM Balikpapan in December 2017, the river currently used with a turbidity parameter of 6 – 24 NTU. Water treatment plants is a production unit to change the properties of water so that it is suitable for consumption. The design of water resources includes various choices among alternatives that that are physically feasible, in general each choice of several alternatives must be based on economic considerations, each alternative that receives serious attention must be stated in units of money before the choice is determined or economically feasible. The purpose of this research is to determine the payback periode and to analyze whether development is feasible from economic (financial) perspective or not. Based on the economic feasibility analysis, the payback periode for the type of reverse osmosis treatment for surface water sources with a capacity of 30 L/s is 16 years an 1 month with selling price or Rp.9.118/m3, to get a payback periode of reverse osmosis type treatment for surface water sources with a capacity of 30 L/s less than 10 years, the selling price of drinking water is Rp.16.000/m3 with a payback periode of 9 years and 3 months.